Conflict Relations of the Municipal Council of Mérida, Yucatán. Actors and Institutions at the End of the Colonial Period - Machuca Gallegos, Laura (Jahrbuch für Geschichte Lateinamerikas, 2025)
The historiography about Municipal councils in the time of Intendency system has placed emphasis on the power struggle between their members and the Intendants. In this work, we will focus on Mérida (Yucatán, New Spain) Municipal council, which particularity was that the conflicts with the Intendents were almost non-existent. The first Intendent had been murdered by the elites’ hands and it was a great lesson for his successors. The members of the municipal council had conflicts about jurisdiction and power with actors belonging to other administrative areas, in particular the city attorney and the lieutenant-assessors. We assume the idea that these struggles show that local power was built from the Municipal councils, from the availability or lack of availability of their members for negotiating the reforms. Although we can talk about success in the economic and fiscal spheres, when we analyze the regions, specially the peripheral, we perceive different strategies of local elites to look after their privileges. In that sense, resistance was one of them, contradicting what did not suit their interests.
Keywords: Municipal Council; Elites; Strategies; Jurisdiction; Power; Resistance.